Kauny Quantum Memory Application Method In Memorizing the Qur'an for Elementary Children in Kauny Qur’anic School Sindang Indramayu - Lina Sopyana (LECTURES: Journal of Islamic and Education Studies, 2022)
This study aims to find out how to apply the Kauny Quantum Memory method in memorizing the Qur'an for elementary school children at Kauny Qur'anic School Al-Hidayah Sindang Indramayu. The type of this research is descriptive qualitative research by taking the research location at Kauny Qur'anic School Al-Hidayah Sindang Indramayu. Data collection was carried out by conducting observations, in-depth interviews and documentation. Data analysis was carried out by reducing data, presenting data and then verifying it and then drawing conclusions. The conclusion of this study is that the application of the Kauny Quantum Memory method in memorizing the Qur'an at Kauny Qur'anic School Al-Hidayah Sindang Indramayu through 3 stages, namely muraja'ah previous memorization, the process of learning to memorize the Qur'an with the method Kauny Quantum Memory then evaluate. The application of the Kauny Quantum Memory method is that the student and the ustadzah prepare their own Al-Qur'an then the ustadzah gives a memorization accompanied by movements to memorize the meaning of the memorized verses. This activity is repeated until the students memorize it. For the evaluation, every day before the end of the class, students do muraja'ah together in one class.